A Peruvian family with a high burden of HTLV-1-associated myelopathy/tropical spastic paraparesis. (21st September 2015) - Alvarez, Carolina; Verdonck, Kristien; Tipismana, Martín; Gotuzzo, Eduardo
Abstract : Human T-lymphotropic virus 1 (HTLV-1) is frequent in Peru; an estimated 1–2% of the Peruvian population carry this retrovirus. HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a chronic disabling disease that affects about 1% of the carriers of HTLV-1. It is not yet known why some HTLV-1-infected people develop HAM/TSP while others do not. In this case report, we present a family with an unusually high burden of HAM/TSP: 5 (the 2 parents and 3 of their children) of 7 HTLV-1 carriers developed the same disease. We describe the clinical presentation and discuss the clustering of disease against the current knowledge of the pathogenesis of HAM/TSP. Families such as this may hold the key to discovering which factors trigger the development of HAM/TSP.